Research on the bearing performance of HSCA high-strength preloaded expansion piles in calcareous sand foundation - Tao Sun; Fang Wang; Jie Liu; Zhenxun Chen; Mingmin Tuo; Yunan Yang (Scientific Reports)
Abstract With the rapid development of infrastructure construction on oceanic reefs, calcareous sand, as the primary medium of these reefs, exhibits unique physical and mechanical properties such as high void ratio, low strength, and susceptibility to particle breakage. These characteristics reduce the bearing capacity and stability of pile foundations in calcareous sand foundations. This study investigates the bearing characteristics of high-strength preloaded expansion piles in calcareous sand foundations, taking into account the influence of HSCA high-performance expansion agent dosage through a series of indoor model tests and in-situ tests. The research delves into the load-settlement curves of expansion piles, the distribution of axial force and side resistance of piles, and the effects of Calcareous sand compaction and reinforcement around the piles. The results indicate that adding the HSCA high-performance expansion agent results in compaction preloading of the Calcareous sand around the pile, significantly increasing the expansion stress on the pile side, thereby enhancing the resistance on both the pile side and pile tip. When the expansion agent dosage is 20%, the ultimate bearing capacity can be increased by 56%, and the ultimate side resistance by 63%. The Coulomb strength theory of non-cohesive soil is employed to accurately calibrate the incremental side resistance of the expansion section. A prediction model for the bearing capacity of the expansion pile is established by combining the side resistance prediction model with the ultimate side resistance load-sharing ratio. The research outcomes provide important guidance for the optimization, design, and construction of high-strength preloaded expansion piles in calcareous sand foundations.